PENGARUH DOSIS BIOSERUM TERHADAP PEMBENTUKAN GAHARU PADA Aquilaria malaccensis Lamk. - Giga Piancita; Indriyanto -; Duryat - (Jurnal Hutan Tropis, 2021)
Natural agarwood takes a long time to be formed in nature, therefore an improvement technique was required in order to increase the productivity of Agarwood.  One of these techniques was Bioserum injection into the Aquilaria malaccensis.  Bioserum is a nutritious liquid necessary for fungi to live, grow and produce the agarwood.  The purpose of the research was to determine the best Bioserum dosage, the best time of Bioserum reacted, and the best interaction between the two factors in the formation of agarwood.  Factorial Completely Randomized Design (FCRD) with two factors, namely the dosage of Bioserum and time of Bioserum reacted in the Aquilaria malaccensis, was employed as the research design.  The dosage of Bioserum applicated was 0 ml, 2 ml, 3 ml, and 4 ml with 3 replications.  The time of Bioserum reacted in the Aquilaria malaccensis was 1 month, 2 months, and 3 months.  The results showed that the best dosage of Bioserum to form the agarwood was 4 ml/hole.  The best time of Bioserum reacted in the Aquilaria malaccensis to form the agarwood was 3 months.  The best of interaction between of the two factors to form the agarwood was the Bioserum dosage of 4 ml with the time of Bioserum reacted of 3 months.